Relación entre la R.S.C. y la felicidad de los empleados: Aplicación al caso de empresas pertenecientes a las provincias de Sevilla y Cádiz - Julio García del Junco; Enrique Nieto Carrami\~nana; Diego Carrera Salguero (Atlantic Review of Economics, 2014)
– The research is oriented to show the possible relation between to main and controversial aspects for the good functioning of a company, such as Corporate Social Responsibility (CSR) and Happiness at the Workplace. With that aim, and in the first place, we try to define, as clear as possible, both terms, from all the existing writings on the subject. Once defined, an exposition follows on the research done by different authors, with the display of the main results obtained though the application of two measuring tools for those concepts: the CSR Diagnosis Questionnaire and the Happiness at the Workplace Survey. These tools have been applied to thirty one companies in Seville and Cadiz in which the relationship between both concepts (Corporate Social Responsibility (CSR) and Happiness at the Workplace) has been established and measured.
Keywords: 330; Corporate Social Responsible; Happiness at the Workplace; CSR Diagnosis Questionnaire; Responsible Agreement